2020
DOI: 10.1038/s41592-020-00971-x
|View full text |Cite
|
Sign up to set email alerts
|

metaFlye: scalable long-read metagenome assembly using repeat graphs

Abstract: Long-read sequencing technologies substantially improved assemblies of many isolate bacterial genomes as compared to fragmented assemblies produced with short-read technologies. However, assembling complex metagenomic datasets remains a challenge even for the state-of-the-art long-read assemblers. To address this gap, we present the metaFlye assembler and demonstrate that it generates highly contiguous and accurate metagenome assemblies. In contrast to short-read metagenomics assemblers that typically fail to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
448
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(451 citation statements)
references
References 79 publications
3
448
0
Order By: Relevance
“…Though not explored in the present work, parameter settings can influence results and should be adjusted depending on the specific research objectives and questions. Nanopore reads were assembled using Canu (v 1.8) 23 and metaFlye (v2.6) 24 . MetaFlye was run using predicted genome sizes of 10 mb, 1 gb, and 10 gb, but was found to produce similar results (not shown), a genome size of 1 gb was chosen.…”
Section: Short Readsmentioning
confidence: 99%
“…Though not explored in the present work, parameter settings can influence results and should be adjusted depending on the specific research objectives and questions. Nanopore reads were assembled using Canu (v 1.8) 23 and metaFlye (v2.6) 24 . MetaFlye was run using predicted genome sizes of 10 mb, 1 gb, and 10 gb, but was found to produce similar results (not shown), a genome size of 1 gb was chosen.…”
Section: Short Readsmentioning
confidence: 99%
“…The Flye (v2.4.2, [ 25 , 26 ]) assembler automatically selects an optimal k-mer size based on an estimated genome size and has a default- (Flye) a meta- (metaFlye) and a plasmid- (plasmidFlye) option for assembly. Besides the default settings of Flye, metaFlye applies an algorithm that tries to generate longer contigs in order to assemble a complete genome, whereas plasmidFlye also includes smaller contigs (excluded in the metaFlye) in the assembly.…”
Section: Introductionmentioning
confidence: 99%
“…OPERA-MS 50 and HybridSPAdes 51 ), but in a preliminary analysis of our data, OPERA-MS produced contigs on average shorter or similar in length to our unassembled long reads (data not shown). Previous literature evaluating assemblers on mock communities has demonstrated that metaFlye, the assembler used in this work, performed well and was able to produce highly contiguous genomes 33,45 . It is important to consider that assembler performance varies by coverage and complexity of microbial communities.…”
Section: Utility Of Assembled Long Readsmentioning
confidence: 84%
“…Nanopore is a relatively new technology and accordingly there are few assembly pipelines available that have been rigorously evaluated 33,[44][45][46][47] . Recently, there has also been emphasis on the potential utility of short reads to improve long-read assemblies through polishing 34 ).…”
Section: Utility Of Assembled Long Readsmentioning
confidence: 99%